Barrier Property, Antimicrobial Susceptibility, and Biodegradability of Waste Cassava Peel Starch/Waste Shrimp Shell Chitosan/Sorbitol Bioplastic Films - Molina, Bianca Isabel B.; Dejuras, Joachim Florenzo C.; Picar, André E.; Veran, Maria Julliana T.; Estrellado, John Ray C. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Barrier properties, antimicrobial susceptibility potential, and biodegradability of bioplastics are critical indicators of bioplastic viability in industrial use, especially when raw materials to the production were sourced from food waste, such as waste cassava peel starch and shrimp shell chitosan. This study aims to investigate these properties from the created bioplastic film primarily consisting of cassava peel starch (CPS) and shrimp shell chitosan (SSCHT), with sorbitol (SOR) as a plasticizer, utilizing green methods and a constrained D-optimal mixture design. Films were assessed via water uptake, water vapor transmission rate, morphology, antimicrobial susceptibility, and biodegradability. Models were generated in terms of water uptake (p = 0.0684) and water vapor transmission rate (p = 0.0013). CPS (p = 0.0008) had a significant effect on water uptake levels due to its hydroxyl groups, which form hydrogen bonds that retain water. On the other hand, water vapor transmission rate was significantly affected by CPS (p = 0.0001) and SOR (p = 0.0001). Although SSCHT (p = 0.0787) was statistically insignificant its acetyl group reduced the hydrophilic nature of CPS. CPS and SOR were found to positively affect weight loss through biodegradation due to increased hydrophilicity and microbial colonization. Scanning electron microscopy (SEM) at 300x magnification revealed visibly smooth morphology of films, while at 1500x and 6500x magnification the films had visible crevices possibly due to greater SSCHT concentrations lower WVTR, and higher CPS concentrations raising water absorption levels.